Engaging consumers online through websites and social media: A gender study of Italian Generation Y clothing consumers. Issue 4 (August 2015) - Nadeem, Waqar; Andreini, Daniela; Salo, Jari; Laukkanen, Tommi
Highlights: We study consumers' engagement online through websites and social networking sites and related peer recommendations. Data has been collected from Generation Y consumer segments who shop online. Online shopping via Facebook and website service quality has positive effect on trust. Peer recommendations have a significantly stronger influence on attitudes of females than they do on attitudes of males. Trust has a positive and significant effect on attitude toward e-tailer and loyalty intentions. Abstract: Consumers increasingly search for, evaluate, and buy items via social media and websites, but little is known about how these activities affect their level of trust, attitudes toward online retailing, and online shopping behaviors. Therefore, this study focuses on how online shopping via Facebook, peer recommendations, and website service quality affect consumer trust, attitudes and loyalty intentions in e-tailing. An online survey was conducted with Generation Y Italian consumers who used Facebook searches of various websites to shop for clothing online. Confirmatory factor analysis was used to validate the constructs, and structural equation modeling (SEM) was employed to test the hypotheses. Findings confirm that website service quality and consumers' predispositions to use Facebook for online shopping directly and positively affect consumer trust toward an e-tailer. In contrast, peer recommendations affect attitude directly rather than indirectly via trust. The results further indicate that peer recommendations have a significantly stronger influence on attitudes of females than they do on attitudes of males.